APPLICATION OF ISLAMIC LEGAL PRINCIPLES IN PUBLIC COMMUNICATION ACTIVITIES: A CASE STUDY AT UIN SYARIF HIDAYATULLAH JAKARTA - Syifa, Syarifah; Mukri, Syarifah Gustiawati; Suherman, Anastasya (JURNAL ILMU SYARIAH, 2024)
UIN Jakarta Publicist Subbag becomes a medium and facilitator between the policy or the direction of the leadership not only with academic Jakarta UIN therein. Subbag public relations has also become a funnel for our publications and dissemination unit and other work units owned by UIN Jakarta. The purpose of this research was to know about the activity of marketing public relations (MPR) Subbag. Publications and Documentation of UIN Jakarta. The research methodology used is the type of qualitative research with engineering data validity using the technique of triangulation which uses the theory of PENCILS (Publications, Events, News, Community involvement, Inform of image, Lobbying and negotiation, and Social responsibility) raised by Philip Kotler. The results showed that seven of the applied theory of PENCILS, aspects of Social responsibility are still held less than optimal; Publications, Events, and News should still be optimized by holding activities and working with national and international media. Recommendations to make Subbag. Publications and Documentation have to do improvements in human resources and forming a special team to manage Public Relations activities.